Prevena™, negative pressure wound therapy applied to closed Pfannenstiel incisions at time of caesarean section in patients deemed at high risk for wound infection. (April 2015) - Anglim, B.; O'Connor, H.; Daly, S.
Abstract The aim of our retrospective study is to report on our experience using the Prevena™ wound system in obese patients undergoing caesarean section delivery. A total of 26 cases were identified from July 2012 to October 2013. The median BMI of these women was 45.3 kg/m2. Elective caesarean sections were performed in 20 women (77%). There were four cases (15%) of superficial dehiscence. Factors associated with wound breakdown were wound infection (p = 0.03), increasing BMI (p < 0.001) and emergency LSCS (p = 0.04). In a logistic regression model the presence of infection was the only factor which remained associated with wound breakdown. Wound disruption is a major cause of morbidity following caesarean section in morbidly obese patients. The wound complication rate in our experience was low with the Prevena™ dressing with no cases of sheath dehiscence, and no patient required a second operation. The presence of infection is the most important factor in wound breakdown and should be the focus for management protocols.